An H α/X-ray orphan cloud as a signpost of intracluster medium clumping. Issue 4 (1st June 2021) - Ge, Chong; Luo, Rongxin; Sun, Ming; Yagi, Masafumi; Jáchym, Pavel; Boselli, Alessandro; Fossati, Matteo; Nulsen, Paul E J; Sarazin, Craig; Edge, Tim; Gavazzi, Giuseppe; Gaspari, Massimo; et al.
ABSTRACT: Recent studies have highlighted the potential significance of intracluster medium (ICM) clumping and its important implications for cluster cosmology and baryon physics. Many of the ICM clumps can originate from infalling galaxies, as stripped interstellar medium (ISM) mixing into the hot ICM. However, a direct connection between ICM clumping and stripped ISM has not been unambiguously established before. Here, we present the discovery of the first and still the only known isolated cloud (or orphan cloud [OC]) detected in both X-rays and H α in the nearby cluster A1367. With an effective radius of 30 kpc, this cloud has an average X-ray temperature of 1.6 keV, a bolometric X-ray luminosity of ∼3.1 × 10 41 erg s −1, and a hot gas mass of ∼10 10 M⊙ . From the Multi-Unit Spectroscopic Explorer ( MUSE ) data, the OC shows an interesting velocity gradient nearly along the east-west direction with a low level of velocity dispersion of ∼80 km s −1, which may suggest a low level of the ICM turbulence. The emission line diagnostics suggest little star formation in the main H α cloud and a low-ionization (nuclear) emission-line regions like spectrum, but the excitation mechanisms remain unclear. This example shows that stripped ISM, even long after the initial removal from the galaxy, can still induce ICM inhomogeneities. We suggest that the magnetic field can stabilize the OC by suppressing hydrodynamic instabilities and thermal conduction. This example also suggests that at least some ICM clumps are multiphase in nature and implies that the ICM clumps can also be traced in H α. Thus, future deep and wide-field H α surveys can be used to probe the ICM clumping and turbulence.